Louvre Museum Wikimedia Commons - Benh LIEU SONG (Wikimedia Commons, 2010)
Notice iconographique issue de Wikimedia Commons. Titre: Louvre Museum Wikimedia Commons. Courtyard of the Museum of Louvre, and its pyramid.
Droits : Licence Creative Commons Attribution-Share Alike 3.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures